Cylowa Zerwa landslide – debris flow forms on Mount Babia Góra (1725) and their development over the last ca. 150 years, Western Carpathians - Łajczak, Adam. Autor; Margielewski, Włodzimierz. Autor; Zielonka, Tomasz. Autor; Pasierbek, Tomasz. Autor; Lamorski, Tomasz. Autor; Kozina, Piotr. Autor; Izworska, Katarzyna. Autor (IGiPZ PAN, 2023)
Cylowa Zerwa landslide – debris flow located on the northern slope of Mt. Babia Góra (1725 m a.s.l.) within the 400 m wide altitude interval (1430-1024 m a.s.l.) is a knowable object which however has not been sufficiently noticed in geomorphological research. This paper, based on geomorphological, geological and dendrochronological investigations, as well as LiDAR data analysis, develops the following issues which describe the functioning of this object during the last ca. 150 years: Cylowa Zerwa in the gravity induced mass movements system of Mt. Babia Góra; relief of the landslide – debris flow and surrounding areas; stages of changes in limit and relief of the mass movement area during the last 150 years; relief elements of the Cylowa Zerwa which are related to debris flow; relationship between dates of the Cylowa Zerwa activation with annual spruce increments. The Cylowa Zerwa, as the only one among Mt. Babia Góra landslides studied, is distinguished by a clear bipartite relief – the upper segment is represented by rock packages, whereas landforms of the middle and lower segments are similar to those originated in the conditions of debris flow. The Cylowa Zerwa landslide – debris flow shows significant education values and it is a remarkable geotourist object.
24 cm
Keywords: Mt. Babia Góra; Western Flysch Carpathians; homoclinal ridge; structural relief; landslide; debris flow; damages in forest; disturbances in touristic movement; geotourism